Poison and High Dose Drug as The Cause of Death in Detective Novels: A Comparison of Agatha Christie’s and Ahmet Ümit’s Works - Tırmıkçıoğlu, Zeynep (The Bulletin of Legal Medicine, 2020)
Objective: The aim of this study was to compare the use of poison or high-dose drugs as the cause of death in western and Turkish literature. Materials and Methods: The works of Agatha Christie and Ahmet Ümit were examined as examples of crime novels. The use of poison or high-dose drugs as the murder weapon and cause of death, the properties of these drugs and substances, and the findings of poisoning were given in the work were evaluated comparatively. Results: In the Agatha Christie novels, various poisons and drugs are given by mixing them into the victim’s food or drink. The victims ’ causes of death are cyanide in “Ten Little Niggers (And Then They Were None)”, “Sparkling Cyanide” and “Mirror Crack’d from Side to Side”; and morphine in “Sad Cypress” and “Death Comes As The End”. In Agatha Christie’s other novels, strychnine, taxine, thallium, phosphorus, arsenic, hemlock, aconitine, belladonna,physostigmine, nicotine and a drug containing barbituric acid have been used as the murder weapon. In the novels of Ahmet Ümit, murder weapons such as knives and pistols appear instead of poisonous preparations that kill the victim. On the other hand, Ahmet Ümit’s novel "İstanbul Hatırası" shows that the victims were neutralized with propofol, a short-acting anesthetic, before being killed, and mivacurium, a neuromuscular blocker, in “Kırlangıç Çığlığı”. The main theme in the novel "Sultanı Öldürmek" is that Fatih Sultan Mehmet may have been poisoned with opium or a similar substance, while in this novel the murder weapon is a...